SIMBOL DALAM PAKELIRAN: PENGANTAR KE ARAH EPISTEMOLOGI SIMBOL - Isa Ansari (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2010)
This article aims to give a short explanation about the theory of symbol in epistemology perspective especially related to the assumption, model, concept and method developed in anthropology. From the assumption point of view, the theory of symbol assume  human as being animal symbolicum who always use their own symbols in interaction so that there is any relationship between text and context. Text is a model of symbol while context is situation which gives meaning to the text (symbol). Positioning symbol in social context means enlarging the meaning of symbol. Meaning is not only what is inherited as we can found in Pakeliran but it is something negotiated because of social interaction process in space and time in society. for the reason, this article offers generic meaning concept and differencial meaning concept in order to avoid the establishing meaning. This implies methodologically especially in data collection, what is data and the interpretation method. In pakeliran, theory of symbol becomes the most important thing because pakeliran is a  symbolic world with various meanings.       Key words: Theory of symbol, Pakeliran, Epistemology of Symbol